Evaluation of Telehealth Delivery of Group Parent-Led Cognitive-Behavioral Therapy During COVID-19: A Pilot Study. (December 2022) - Byrne, Gary; Vickers, Louise; Ni Longphuirt, Eithne; Cunningham, Roisin
The COVID-19 pandemic has led to governments around the world imposing varying levels of restrictions and lockdowns leading to home confinement and closure of schools. Children with autism spectrum disorder (ASD) and their families may be particularly susceptible to increased anxiety. A growing evidence base has developed for parent-led cognitive-behavioral therapy (CBT) for child anxiety disorders. The current pilot study aimed to evaluate the preliminary clinical utility (acceptability, feasibility, and efficacy) of a parent-led CBT program in Dublin, Ireland, through an online format. Parents of nine children completed the program. The child did not participate in any part of the online program. Acceptability was strong, and although technical issues were problematic at times, all families completed the program. Preliminary efficacy analysis is mixed, with significant reductions on youth anxiety as measured by clinician-administered questionnaire but no reduction in parent-report measures. Findings suggest that the online program is acceptance, feasible, and effective.